Occurrence of connected clusters in motility-induced phase-separated states of persistent active particles at zero temperature - Schmiedeberg, Michael (EPL - Europhysics Letters, 2023)
To study the interplay of the formation of clusters of overlapping particles and motility-induced phase separation in the zero temperature limit in two dimensions, we consider a simple model system consisting of a bidisperse mixture of disks that are only subject to a repulsion force in case of overlaps and an active force. The orientation of the disks is chosen randomly in the beginning and does not change anytime during the simulation thus corresponding to an infinite persistence length. Simulations with our model system reveal that clusters of overlapping particles occur in the dense phase of a phase-separated state in case of intermediate values of the ratio of active to repulsive force. However, for smaller activities there are only a few overlaps between the particles in the dense phase and the coexistence region ends at a packing fraction below the onset of the formation of clusters with overlapping particles. For large activities small clusters corresponding to small patches of the dense phase are found that are unstable due to the activity. Finally, the occurrence of connected clusters affects the phase separation. Our findings on how cluster formation and phase separation are related are relevant to many active particle systems as after adding thermal noise our model system corresponds to a system of active Brownian particles that have been intensely studied in recent years. Further extensions by adding friction, inertia, or more complex interactions are possible.<br
Keywords: active particles; phase separation; clustering; non-equilibrium